Liquid-phase blocking sandwich enzyme-linked immunosorbent assay for detection of antibodies against foot-and-mouth disease virus in water buffalo sera - Araújo, J. P. [UNESP]; Montassier, H. J. [UNESP]; Pinto, A. A. [UNESP] (My University, 1996)
Objective - To develop and apply the liquid-phase blocking sandwich ELISA (BLOCKING-ELISA) for the quantification of antibodies against foot-and-mouth disease virus (FMDV) strains O1 Campos, A24 Cruzeiro, and C3 Indaial. Design - Antibody quantification. Sample Population-158 water buffalo from various premises of São Paulo State-Brazil. The sera were collected either from systemically vaccinated or nonvaccinated animals. Procedure - The basic reagents of BLOCKING-ELISA (capture and detector antibodies, virus antigens, and conjugate) were prepared and the reaction was optimized and standardized to quantify water buffalo antibodies against FMDV. An alternative procedure based on mathematical interpolation was adopted to estimate more precisely the antibody 50% competition titers in the BLOCKING-ELISA. These titers were compared with the virus-neutralization test (VNT) titers to determine the correlation between these techniques. The percentages of agreement, cutoff points, and reproducibility also were determined. Results - The antibody titers obtained in the BLOCKING-ELISA had high positive correlation coefficients with VNT, reaching values of 0.90 for O1 Campos and C3 Indaial, and 0.82 for the A24 Cruzeiro (P <0.0005). The cutoff points obtained by use of the copositivity and conegativity curves allowed determination of high levels of agreement between BLOCKING-ELISA and VNT antibody titers against the 3 FMDV strains analyzed. Conclusions - The results characterized by high correlation coefficients, levels of agreement, and reproducibility indicate that the BLOCKING-ELISA may replace the conventional VNT for detection and quantification of antibodies from water buffalo sera to FMDV.